General Discussion Undecided where to post - do it here. |
Reply to Thread New Thread |
![]() |
#1 |
|
Given the equation x^2+kx+1=0 and x^2-x +k=0 has common roots, find the values of k and the common roots.
Somebody asked me for help on this question but I'm kinda stumped as well. Anyway here's what I came up with, I have a feeling that I'm wrong though. Code: Code
x^2 + kx + 1 = 0 b^2 - 4ac = 0 k^2 - 4 (1)(1) k^2 = 4 k = 2 x^2 + 2x + 1 = 0 (x+1) (x+1) = 0 x = -1 ---------------------------------------------------- X^2 - x + k = 0 b^2 - 4ac = 0 (-1)^2 - 4(1)(k) 1 - 4k = 0 -4k = -1 k = 1/4 x^2 - x + 1/4 [ -b +/- sqrt b^2 - 4ac ] / 2a [ -(-1) +/- sqrt (-1)^2 - 4(1)(1/4) ] / 2(1) 1 +/- 0 / 2 x = 1/2 Is my answer correct? |
![]() |
![]() |
#2 |
|
|
![]() |
![]() |
#3 |
|
For a general quadratic equation, ax^2 + bx^2 + c = 0:
roots, x = (-b +/- sqrt(b^2 - 4ac))/2a So, solving for the two equations, the common root would be (-k +/- sqrt(k^2-4))/2 = (-1 +/- sqrt(1-4k))/2 It turns out k = 1 satisfies the equation And so the common roots x = (1 +/- i*sqrt(3))/2 ...I think. |
![]() |
![]() |
#4 |
|
|
![]() |
![]() |
#5 |
|
|
![]() |
![]() |
#6 |
|
This is your homework not mine :P I've tried plugging back mine and they equal to 0. Does that mean that my answer is correct? I'm not sure myself ![]() |
![]() |
![]() |
#7 |
|
Whoops I think the roots are supposed to be x = (1 +/- i*sqrt(3))/2
I had an extra (-) there edit: BTW, your answers are incorrect in the sense that you did not have common roots that satisfy both equations. edit: and yet...I found an error in my post above. Sigh. Will try to work it out. For a general quadratic equation, ax^2 + bx^2 + c = 0: roots, x = (-b +/- sqrt(b^2 - 4ac))/2a So, solving for the two equations, the common root would be (-k +/- sqrt(k^2-4))/2 = (-1 +/- sqrt(1-4k))/2 [ERROR] It turns out k = 1 satisfies the equation And so the common roots x = (1 +/- i*sqrt(3))/2 ...I think. Unfortunately k = 1 is *not* the solution. I mostly did it by inspection (and I made and error)...so now I'm hand-calculating this and I've reached a point where I don't feel like working out the algebra. Perhaps I'm misinterpreting the term "common roots". I don't feel like solving the following: (-k +/- sqrt(k^2 - 4))/2 = (1 +/- sqrt(1-4k))/2 |
![]() |
![]() |
#8 |
|
|
![]() |
![]() |
#9 |
|
Yeah it's annoying me now.
Feels like it's too complicated, so I looked for some way to verify the existance of common roots. Then I found this online: Code: Code
Theorem: Consider the two quadratic equations a m2 + b m + c = 0 a'm2 + b'm + c'= 0 with a and a' not zero, together with 3 determinants |b c| |a c| |a b| A = | | B = - | | C = | | |b' c'| |a' c'| |a' b'| The equations have a common root if and only if A.C = B2. The expression A.C = B2 is called the eliminant of Sylvester. Proof: We multiply the first equation with a', the second one with a, and we calculate the difference of these two results. (ba' - a'b) m + (a'c - ac') = 0. From this, the system of the two quadratic equations is equivalent with / (ba' - a'b) m + (a'c - ac') = 0. \ a m2 + b m + c = 0 These equations have a common root if and only if the root of the first one, is a root of the second equation. The root of the first equation is (a'c - a c') / (b'a - a b') = B/C . The condition then is: a (B/C)2 + b (B/C) + c = 0 a B2 + b B C + c C2 = 0 a B2 = -C ( b B + c C) ... a B2 = a ( C A) and since a is not 0 A.C = B2 If I worked out the math right, the two quadratic equations won't meet this requirement (B2 really means B^2 = B.B but the page didn't paste correctly). Perhaps it's late and I suck at math. Check with your friend to make sure he gave you the right problem? edit: see next post (I misinterpreted the theorem above...I thought A, B, and C were matrices when they were actually determinants :/). |
![]() |
![]() |
#10 |
|
|
![]() |
![]() |
#11 |
|
Well, I tried doing it in maple. I got one real answer and two complex answers for k. However the real answer is really complex and has stuff like thrid roots in it so maybe its wrong...
![]() First thing i did was work out roots in terms of k. Then i tried putting each root equal to another from the other equation to see if anything came out. "k1" was my real answer, putting that back into the equations they shared an identical root. so if k = -2.658967080 and x=2.205569430 then both equations are zero. |
![]() |
![]() |
#12 |
|
|
![]() |
![]() |
#13 |
|
|
![]() |
![]() |
#14 |
|
I'm going nuts. My friend just got back to me about the answer that I asked her for. .... in your own solution... what makes you think b^2 - 4ac = 0??? it must be greater or equal to 0 because it has to be rooted - nothing says it has to be 0. |
![]() |
Reply to Thread New Thread |
Currently Active Users Viewing This Thread: 1 (0 members and 1 guests) | |
|